Konseling Kelompok Rational Emotive Behaviour Therapy Berbasis Nilai Budaya Jawa Untuk Meningkatkan Kebermaknaan Hidup Pada Masa Pandemi Covid-19 - Dewi Lianasari; Muhammad Japar (Kuras Institute, 2022)
The meaning of life is a condition in which the individual has a high motivation for the life lived to achieve the goals and happiness of his life. However, the Covid-19 pandemic has also caused problems in various fields, one of which has an impact on decreasing life goals, life satisfaction, freedom of choice, passions, and responsibility for life. The purpose of this study is to help people improve their survival through counseling groups rational emotive behaviour therapy based on Javanese cultural values. This research method pre-experiments one group pretest posttest design with random sampling techniques. The results showed that counseling the rational emotive behaviour therapy group based on Javanese cultural values succeeded in improving the meaning of people's lives during the Covid-19 pandemic as evidenced by the results of statistical tests with the Wilcoxon Test seen by A symp. Sig/Asymptotic significance of two sides is 0.043 and the probability value is less than 0.05. This confirms that the intervention in the form of Rational Emotive Behavior Therapy counseling services based on Javanese Cultural Values Can Increase the Meaningfulness of Life During the Covid-19 Pandemic.